Risk assessment and seroprevalence of SARS-CoV-2 infection in healthcare workers of COVID-19 and non-COVID-19 hospitals in Southern Switzerland - Luca Piccoli; Paolo Ferrari; Giovanni Piumatti; Sandra Jovic; Blanca Fernandez Rodriguez; Federico Mele; Isabella Giacchetto-Sasselli; Tatiana Terrot; Chiara Silacci-Fregni; Elisabetta Cameroni; Stefano Jaconi; Nicole Sprugasci; et al. (Elsevier, 2021)
Summary: Background: Hospital healthcare workers (HCW), in particular those involved in the clinical care of COVID-19 cases, are presumably exposed to a higher risk of acquiring the disease than the general population. Methods: Between April 16 and 30, 2020 we conducted a prospective, SARS-CoV-2 seroprevalence study in HCWs in Southern Switzerland. Participants were hospital personnel with varying COVID-19 exposure risk depending on job function and working site. They provided personal information (including age, sex, occupation, and medical history) and self-reported COVID-19 symptoms. Odds ratio (OR) of seropositivity to IgG antibodies was estimated by univariate and multivariate logistic regressions. Findings: Among 4726 participants, IgG antibodies to SARS-CoV-2 were detected in 9.6% of the HCWs. Seropositivity was higher among HCWs working on COVID-19 wards (14.1% (11.9-16.5)) compared to other hospital areas at medium (10.7% (7.6-14.6)) or low risk exposure (7.3% (6.4-8.3)). OR for high vs. medium wards risk exposure was 1.42 (0.91-2.22), P = 0.119, and 1.98 (1.55-2.53), P<0.001 for high vs. low wards risk exposure. The same was for true for doctors and nurses (10.1% (9.0-11.3)) compared to other employees at medium (7.1% (4.8-10.0)) or low risk exposure (6.6% (5.0-8.4)). OR for high vs. medium profession risk exposure was 1.37 (0.89-2.11), P = 0.149, and 1.75 (1.28-2.40), P = 0.001 for high vs. low profession risk exposure. Moreover, seropositivity was higher among HCWs who had household exposure to COVID-19 cases compared to those without (18.7% (15.3-22.5) vs. 7.7% (6.9-8.6), OR 2.80 (2.14-3.67), P<0.001). Interpretation: SARS-CoV-2 antibodies are detectable in up to 10% of HCWs from acute care hospitals in a region with high incidence of COVID-19 in the weeks preceding the study. HCWs with exposure to COVID-19 patients have only a slightly higher absolute risk of seropositivity compared to those without, suggesting that the use of PPE and other measures aiming at reducing nosocomial viral transmission are effective. Household contact with known COVID-19 cases represents the highest risk of seropositivity. Funding: Henry Krenter Foundation, Ente Ospedaliero Cantonale and Vir Biotechnology.